Conformational transitions of the serotonin 5-HT3 receptor. (8th November 2018) - Polovinkin, Lucie; Hassaine, Ghérici; Perot, Jonathan; Neumann, Emmanuelle; Jensen, Anders; Lefebvre, Solène; Corringer, Pierre-Jean; Neyton, Jacques; Chipot, Christophe; Dehez, Francois; Schoehn, Guy; Nury, Hugues
Abstract The serotonin 5-HT3 receptor is a pentameric ligand-gated ion channel (pLGIC). It belongs to a large family of receptors that function as allosteric signal transducers across the plasma membrane1, 2 ; upon binding of neurotransmitter molecules to extracellular sites, the receptors undergo complex conformational transitions that result in transient opening of a pore permeable to ions. 5-HT3 receptors are therapeutic targets for emesis and nausea, irritable bowel syndrome and depression3 . In spite of several reported pLGIC structures4–8, no clear unifying view has emerged on the conformational transitions involved in channel gating. Here we report four cryo-electron microscopy structures of the full-length mouse 5-HT3 receptor in complex with the anti-emetic drug tropisetron, with serotonin, and with serotonin and a positive allosteric modulator, at resolutions ranging from 3.2 Å to 4.5 Å. The tropisetron-bound structure resembles those obtained with an inhibitory nanobody5 or without ligand9 . The other structures include an 'open' state and two ligand-bound states. We present computational insights into the dynamics of the structures, their pore hydration and free-energy profiles, and characterize movements at the gate level and cation accessibility in the pore. Together, these data deepen our understanding of the gating mechanism of pLGICs and capture ligand binding in unprecedented detail. Cryo-electron microscopy of the serotonin 5-HT3 receptor in complex with various ligands yields four distinct structures, capturing serotonin binding in detail and increasing understanding of the gating mechanism of the receptor.